2010
DOI: 10.1007/s00464-010-1048-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of in-hospital length of stay after laparoscopic ventral hernia repair: results of multivariate logistic regression analysis

Abstract: Mesh size, incarcerated hernia, patient age, and complex hernia predict longer length of stay after laparoscopic ventral hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…The morbidity and mortality rates of elderly patients were similar to those of younger age. Two studies reported longer length of stay and later return to normal activities [26,27]. The aforementioned studies have weak statistical power and short follow-up.…”
Section: Luis Sanchez Lapo Bencinimentioning
confidence: 93%
See 1 more Smart Citation
“…The morbidity and mortality rates of elderly patients were similar to those of younger age. Two studies reported longer length of stay and later return to normal activities [26,27]. The aforementioned studies have weak statistical power and short follow-up.…”
Section: Luis Sanchez Lapo Bencinimentioning
confidence: 93%
“…Incarcerated hernia, together with mesh size, patient age, and complex hernia are predicting factors about longer length of stay [27]. …”
Section: Acute Presentation: Emergencymentioning
confidence: 99%
“…[11, 14] Several previous studies have examined the effect of patient and procedural characteristics on hospital stay after LVHR. [15, 16] These studies demonstrate that more complex procedures associated with long operative duration due to lysis of adhesions or large hernia defects are associated with prolonged LOS. In our analysis, we used operative time and mesh size as markers of procedural complexity.…”
Section: Discussionmentioning
confidence: 99%
“…O tempo de internação hospitalar, após uma determinada cirurgia, também deve ser considerado na logística de pacientes, segundo Kurian et al (2010). Renata Pereira Oliveira, Augusto da Cunha Reis, Alexandre de Carvalho Castro como benchmarking, pesquisa operacional, gestão lean e six sigma, poderiam ser adotados para melhorar a logística do paciente em saúde.…”
Section: Análise De Conteúdounclassified